2008
DOI: 10.1103/physrevb.78.125113
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical superlens by a coordinate transformation

Abstract: Cylinder-shaped perfect lens deduced from the coordinate transformation method is proposed.The previously reported perfect slab lens is noticed to be a limiting form of the cylindrical lens when the inner radius approaches infinity with respect to the lens thickness. Connaturality between a cylindrical lens and a slab lens is affirmed by comparing their eigenfield transfer functions. We numerically confirm the subwavelength focusing capability of such a cylindrical lens with consideration of material imperfect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
227
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(241 citation statements)
references
References 23 publications
10
227
0
1
Order By: Relevance
“…Interestingly, both have been also shown to obey the same dispersion relation 95 . As we mentioned above the physics underlying the formation of the EM in the present case is similar to the one discussed for the monoatomic nanowires [91][92][93] , and it can not be retrieved in the classical calculations.…”
Section: Optical Response Of Charged Monoatomic Metallic Nanodisksupporting
confidence: 50%
See 3 more Smart Citations
“…Interestingly, both have been also shown to obey the same dispersion relation 95 . As we mentioned above the physics underlying the formation of the EM in the present case is similar to the one discussed for the monoatomic nanowires [91][92][93] , and it can not be retrieved in the classical calculations.…”
Section: Optical Response Of Charged Monoatomic Metallic Nanodisksupporting
confidence: 50%
“…This mode is axially symmetric and it is characterized by an antisymmetric charge density distribution induced at the top and bottom surfaces of the nanodisk. Different from the propagating edge plasmons discussed classically 20,[23][24][25]73,95 , the edge mode of the nanodisk found here stems from lateral coordinate dependence of the confining potential and it is similar to the transverse edge mode reported in quantum calculations of the monoatomic wires [91][92][93] For nanodisks negatively charged by electron doping several quantum effects are important:…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…DePrince et al showed that plasmon modes emerge from a linear hydrogen atomic chain because the charge density oscillates continuously throughout the system [11]. Plasmon resonance is also observed in noble metal atomic chains in the presence of localized d electrons [12,13]. Nayyar et al recently identified the local plasmonic electron oscillations around dopant atoms in transition-metal-doped gold chains [14].…”
Section: Introductionmentioning
confidence: 99%